A Analysis of Machine Maintenance System Using Preventive Maintenance Method with Always Better Control (ABC) Classification and Modular Design - Mohammad Fadhli; Joumil Aidil Saifuddin Z.S; Yekti Condro Winursito (ITEJ (Information Technology Engineering Journals), 2025)
Companies must pay special attention to the machines used to make goods because if the machine is damaged, the resulting product will be damaged or the product will take a long time in the production process. By performing regular machine maintenance, companies can maintain and extend the service life of the machine. PT XYZ is a company in Indonesia that has an installed production capacity of 29 million tons of cement per year. The company uses a continuous production system, namely ensuring that all machines are in good condition so that the production process does not experience delays or losses. The results of observations show that the packer operation is the production process with the longest waiting time, with the Roto packer 638PM1 being the machine with the longest waiting time. Corrective and preventive maintenance are two types of maintenance currently used, and the current preventive maintenance strategy is currently suboptimal. This study aims to develop an efficient preventive maintenance system by providing preventive maintenance recommendations using the design modularity method and the Always Better Control (ABC) classification. By combining the classification of machines between critical levels and the utility value of each machine component, operational efficiency will increase, the risk of production disruptions caused by critical component shortages and unnecessary storage costs will be reduced. By applying this method, the total maintenance cost incurred is Rp. 771,782,456, this result has a difference of Rp. 406,113,204 smaller than the total maintenance cost currently used by the company, which is Rp. 1,177,895,660. The results demonstrate that the proposed maintenance method is effective and feasible, achieving a 34.47% cost efficiency improvement over the company’s current maintenance system.